'Behaviour: Marking': Charlotte Prodger's territoriality. (1st September 2021) - Cuthbertson, Tom
This article analyses single-channel videos by the Turner Prize-winning artist Charlotte Prodger (b.1974), identifying in these works very particular forms of territoriality. As part of the broader drive towards accumulation found in Prodger's autobiographical filmmaking, these videos continually collect new territories: characterized by a restless spatial mobility, they move repeatedly from location to location, amassing huge amounts of spatial information. This information is arranged in an ever-expanding matrix ‐ a grid-like structure that allows Prodger to bring the very different spaces she assembles into active conversation, amongst themselves and with her. As she fosters deeply subjective dialogues and connections between these spaces, Prodger marks them, leaving traces behind in ways that deliberately mimic recognizably animal territorial practices and patterns of behaviour. Merging human and non-human behaviours, Prodger investigates the disruptive possibilities of what Jack Halberstam has presented as a queer form of 'wildness', and unsettles categories of gender and sexuality along with the spatialized mechanisms of sexual difference that support them. By marking territory in such 'wild' ways, Prodger proposes other modes of knowing and understanding, found at the meeting point of the subjective, the social and the environmental. In so doing, Prodger challenges the rules dictating which bodies, lives and behaviours belong where, as well as who is allowed to occupy and lay claim to certain spaces.